Pendampingan Siswa dan Masyarakat dalam Bidang Pendidikan, Keterampilan, Ekstrakurikuler dan Kepedulian terhadap Lingkungan - Nani Apriyani; Rita Rahmaniati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Community growth and rapid technological development not only have a positive impact on life but also have a negative impact. The problem today is the decrease of public awareness in reading and writing Al Qur'an, reading literacy culture from an early age, and the importance of having skills of handicraft and participating in extracurricular activities also preserving the environment. This community service activity aims to maintain and re-grow the reading literacy culture, the penchant for reading and writing Al Qur'an, having skills of handicraft, taking extracurricular activities and protecting the environment. To instill this personality, a long period of time is needed so it must be done as early as possible. The targets in this community service are early childhood and society. These activities were held in May to June 2017 in several places by conducting education and mentoring. The participants have given a positive response with high enthusiasm. This community service still needs to be carried out similar activities continuously to get personality according to these goals.